Fabrication of NiO-Y:BaZrO3 composite anode for thin film-protonic ceramic fuel cells using tape-casting - Bae, K.; Noh, H.-S.; Jang, D.Y.; Kim, M.; Kim, H.J.; Hong, J.; Lee, J.-H.; Kim, B.-K.; Son, J.-W.; Shim, J.H. (Korean Ceramic Society, 2015)
Optimization of the fabrication process of NiO-yttrium doped barium zirconate (BZY) composite anode substrates using tapecasting for high performance thin-film protonic ceramic fuel cells (PCFCs) is investigated. The anode substrate is composed of a tens of microns-thick anode functional layer laminated over a porous anode substrate. The macro-pore structure of the anode support is induced by micron-scale polymethyl methacrylate (PMMA) pore formers. Thermal gravity analysis (TGA) and a dilatometer are used to determine the polymeric additive burn-out and sintering temperatures. Crystallinity and microstructure of the tape-cast NiO-BZY anode are analyzed after the sintering.
Keywords: Anodes; Barium zirconate; Ceramic materials; Electrodes; Fuel cells; Gas fuel purification; Polymethyl methacrylates; Pore structure; Sintering; Substrates; Thin films; Anode functional layer; Composite anodes; NiO-BZY; Polymeric additives; Porous anode substrate; Sintering temperatures; Tape casting; Thermal gravity analysis; Protonic ceramic fuel cells (PCFC)